2006
DOI: 10.1016/j.jcrs.2005.12.104
|View full text |Cite
|
Sign up to set email alerts
|

Surgically induced astigmatism after phacoemulsification in eyes with mild to moderate corneal astigmatism

Abstract: Seven weeks after small-incision phacoemulsification, the CCTI induced less SIA than the CCOI; however, there were no significant differences in the final UCVA and BCVA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
1
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(49 citation statements)
references
References 32 publications
2
44
1
2
Order By: Relevance
“…The outcomes of a previous randomized clinical trial 2 were analyzed. The trial comprised 62 eyes with cataract and mild to moderate corneal astigmatism (!2.60 diopters [D]) that had phacoemulsification by a single surgeon (V.M.)…”
Section: Methodsmentioning
confidence: 99%
“…The outcomes of a previous randomized clinical trial 2 were analyzed. The trial comprised 62 eyes with cataract and mild to moderate corneal astigmatism (!2.60 diopters [D]) that had phacoemulsification by a single surgeon (V.M.)…”
Section: Methodsmentioning
confidence: 99%
“…[8][9][10][11] The influence of incision size on SIA has been studied by different authors. Kohnen et al 8 found a mean SIA of 0.47 G 0.32 D after 3.6 to 3.8 mm temporal incisions.…”
Section: Discussionmentioning
confidence: 99%
“…We have taken into consideration studies performed on the phaco incisions by Borasio et al 10 and Masket et al 11 .…”
Section: Planning Of Incisionmentioning
confidence: 99%